2013
DOI: 10.1021/sc4000225
|View full text |Cite
|
Sign up to set email alerts
|

Nanocellulose Life Cycle Assessment

Abstract: Nanocellulose is a nascent and promising material with many exceptional properties and a broad spectrum of potential applications. Because of the unique and functional materials that can be created using nanocellulose, pilot-scale development for commercialization has begun. Thus a thorough understanding of its environmental impact, covering the whole life cycle of nanocellulose, becomes the foundation for its long-term sustainable success. In this current study, four comparable lab scale nanocellulose fabrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
166
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(177 citation statements)
references
References 38 publications
3
166
0
3
Order By: Relevance
“…41 Though limited, current data suggest that CNs exhibit very good biocompatibility and low toxicity. 41,42 There are significant differences between CNs and CNTs that limit its complete substitution. Unlike CNTs, unmodified CNs are not electrically conductive nor photocatalytic.…”
Section: Considerations For Cellulose Nanomaterial-based Developmementioning
confidence: 97%
“…41 Though limited, current data suggest that CNs exhibit very good biocompatibility and low toxicity. 41,42 There are significant differences between CNs and CNTs that limit its complete substitution. Unlike CNTs, unmodified CNs are not electrically conductive nor photocatalytic.…”
Section: Considerations For Cellulose Nanomaterial-based Developmementioning
confidence: 97%
“…The interest in these materials is explained by their advantageous basic properties, such as renewability, high mechanical strength, large specific surface area, high aspect ratios, barrier properties, optical behavior, biodegradability, and biocompatibility (Eichhorn et al 2009). A majority of the environmental impact of nanocellulose fabrication depends on both the chemical modification and mechanical treatment route chosen (Li et al 2013). Use of cotton linters reduces the entire pulping process, as required in wood processing, because the raw material contains more than 90% cellulose.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Life cycle analyses have shown that all these fabrication processes exhibit prominent environmental advantages over other nanomaterials such as carbon nanotubes. [18,19] Among the fabrication processes, the enzymatic pretreatment route and mechanical agitation exhibit the lowest environmental impact. However, enzyme stability and the energy required for mechanical agitation are important cost factors.…”
Section: Doi: 101002/gch2201700045mentioning
confidence: 99%